Chromosomal position and specific demethylation in enhancer sequences of germ line-transmitted retroviral genomes during mouse development. - Jähner, D (1985)
The methylation pattern of the germ line-transmitted Moloney leukemia proviral genome was analyzed in DNA of sperm, of day-12 and day-17 embryos, and of adult mice from six different Mov substrains. At day 12 of gestation, all 50 testable CpG sites in the individual viral genomes as well as sites in flanking host sequences were highly methylated. Some sites were unmethylated in sperm, indicating de novo methylation of unique DNA sequences during normal mouse development. At subsequent stages of development, specific CpG sites which were localized exclusively in the 5' and 3' enhancer regions of the long terminal repeat became progressively demethylated in all six proviruses. The extent of enhancer demethylation, however, was tissue specific and strongly affected by the chromosomal position of the respective proviral genome. This position-dependent demethylation of enhancer sequences was not accompanied by a similar change within the flanking host sequences, which remained virtually unchanged. Our results indicate that viral enhancer sequences, but not other sequences in the M-MuLV genome, may have an intrinsic ability to interact with cellular proteins, which can perturb the interaction of the methylase with DNA. Demethylation of enhancer sequences is not sufficient for gene expression but may be a necessary event which enables the enhancer to respond to developmental signals which ultimately lead to gene activation.